The use of corticosteroids in the treatment of ulcerative colitis: A brief overview - Radlović Aleksandar; Safiye Teodora; Mahmutović Elvis (Arhiv za farmaciju)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by the relapsing inflammation of the colonic mucosa. Corticosteroids have long been a cornerstone in the management of moderate to severe UC, particularly during acute flares. This review aims to provide a focused overview of the rationale behind corticosteroid use, including their mechanisms of action, clinical efficacy, and challenges in everyday practice such as steroid dependency, adverse effects, and inappropriate long-term use. Despite their effectiveness in inducing remission, corticosteroids are not suitable for maintenance therapy and should be used judiciously in combination with other treatments. Current best-practice recommendations emphasize minimizing steroid exposure and encouraging the use of steroid-sparing agents. Close monitoring by specialists remains essential for optimizing outcomes and ensuring patient safety.